2022
DOI: 10.3389/fpls.2022.907231
|View full text |Cite
|
Sign up to set email alerts
|

Water and Nitrogen Management at the Booting Stage Affects Yield, Grain Quality, Nutrient Uptake, and Use Efficiency of Fragrant Rice Under the Agro-Climatic Conditions of South China

Abstract: The present study was conducted to assess the effects of water and nitrogen applications at the booting stage on yield, grain quality, and nutrient use efficiencies in fragrant rice in the early (March–July) and late (July–November) seasons of 2013. The experiment was comprised of two fragrant rice cultivars, i.e., Nongxiang 18 and Basmati; three nitrogen levels, i.e., 0 kg N ha−1 (N0), 30 kg N ha−1 (N1), and 60 kg N ha−1 (N2); and three water levels, i.e., 2–4 cm water layer well-watered (W0), water with a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“… 36 , 37 In contrast, a representative of C3 plants, rice, is highly dependent on water and nutrient supply to achieve the expected yield. 38 With respect to quantitative VOC differences between rice and sorghum, it is possible to infer from a large volume of indirect evidence that C3 and C4 metabolic networks might be actually involved in the empirically observed differential emission of VOCs in our experiments. Previously, Niinemets and Reichstein 39 , 40 concluded that the amounts of VOCs released by plants are affected by stomatal conductance, which, reportedly, tends to be lower in C4 compared to C3 plants, especially under high light conditions.…”
Section: Discussionmentioning
confidence: 80%
“… 36 , 37 In contrast, a representative of C3 plants, rice, is highly dependent on water and nutrient supply to achieve the expected yield. 38 With respect to quantitative VOC differences between rice and sorghum, it is possible to infer from a large volume of indirect evidence that C3 and C4 metabolic networks might be actually involved in the empirically observed differential emission of VOCs in our experiments. Previously, Niinemets and Reichstein 39 , 40 concluded that the amounts of VOCs released by plants are affected by stomatal conductance, which, reportedly, tends to be lower in C4 compared to C3 plants, especially under high light conditions.…”
Section: Discussionmentioning
confidence: 80%
“…Low water levels generally led to an increase in grain 2-AP contents, possibly due to enhanced endogenous proline contents that later converts into 2-AP. , Moderate drought (soil water potential −25 kPa) at the booting and grain filling stage enhanced the grain 2-AP contents. , Thus, a proper irrigation schedule together with N application may have a significant impact on aroma biosynthesis in fragrant rice. Water–nitrogen interaction (e.g., application of 30 kg ha –1 N fertilizer and −20 kPa irrigation water at the tillering stage) significantly increases grain 2-AP contents in rice as well as increases the yield. , The aromatic quality of rice is also affected by factors such as the time of field draining and harvesting in relation to physiological maturity, moisture content, and weather conditions . Low planting density and early harvesting can boost aroma content, and the best aroma (aroma score 3) can be found 20 days after 50% flowering .…”
Section: Advancement In Agro-management Practices To Improve the Arom...mentioning
confidence: 99%
“…10 On the other hand, growing late-season rice is conducive to high yield with better grain quality owing to suitable temperature and light intensity in south China. 11 Deng et al 12 reported that the yield of late season rice and fertilizer use efficiency were improved by N fertilizer management. Previous studies reported that nitrogen application had a significant effect on leaf area index and leaf photosynthesis rate.…”
Section: Introductionmentioning
confidence: 99%